THE SECRET PASSAGE: HOW AMZALAK AND SALAZAR HELPED LUDWIG VON MISES ESCAPE THE NAZIS - MATA, OSCAR (REVISTA PROCESOS DE MERCADO, 2025)
World War II was marked by the persecution and forced displace- ment of millions of people. Among them was Ludwig von Mises, one of the most brilliant minds in economics, whose ideas chal- lenged the growing totalitarianism in Europe. Although there are few written records of his escape from Europe, this article pro- vides several previously unpublished details, based on rare and never-before-published documents. These documents, discovered in Swiss and Portuguese archives, reveal a previously unknown side of Mises’s journey. They show not only his elaborate escape plan, but also the crucial support of figures such as Moisés Amzalak, president of the Jewish commu- nity in Lisbon, and Oliveira Salazar, the well-known President of the Council of Ministers of Portugal. In a journey marked by count- less risks and the need for discretion, Ludwig von Mises became “Louis Mises”—a name that, as we will see, was both a strategy and an enigma for historians. This article is therefore a rediscov- ery, exploring Mises’s journey in a new light, revealing how Portu- gal served as a safe haven for one of the greatest intellectuals of the twentieth century.